Local Pulmonary Immunological Biomarkers in Tuberculosis - Morrison, Hazel; McShane, Helen (Frontiers in Immunology, 2021)
Regardless of the eventual site of disease, the point of entry for Mycobacterium tuberculosis (M.tb) is via the respiratory tract and tuberculosis (TB) remains primarily a disease of the lungs. Immunological biomarkers detected from the respiratory compartment may be of particular interest in understanding the complex immune response to M.tb infection and may more accurately reflect disease activity than those seen in peripheral samples. Studies in humans and a variety of animal models have shown that biomarkers detected in response to mycobacterial challenge are highly localised, with signals seen in respiratory samples that are absent from the peripheral blood. Increased understanding of the role of pulmonary specific biomarkers may prove particularly valuable in the field of TB vaccines. Here, development of vaccine candidates is hampered by the lack of defined correlates of protection (COPs). Assessing vaccine immunogenicity in humans has primarily focussed on detecting these potential markers of protection in peripheral blood. However, further understanding of the importance of local pulmonary immune responses suggests alternative approaches may be necessary. For example, non-circulating tissue resident memory T cells (TRM) play a key role in host mycobacterial defences and detecting their associated biomarkers can only be achieved by interrogating respiratory samples such as bronchoalveolar lavage fluid or tissue biopsies. Here, we review what is known about pulmonary specific immunological biomarkers and discuss potential applications and further research needs.